Penerapan strategi pemasaran dalam meningkatkan volume penjualan - wardana, Syahla nabil; iqbal fasa , muhammad (PT. Intelek Cendikiawan Nusantara, 2024)
This study aims to provide new insights and ideas in developing unique marketing strategies and creativity in marketing because with uniqueness and creativity, the brand performance of a product is maintained and developed for products or services. Basically, every company has a marketing strategy that can help the company achieve its goals and desired results. Marketing strategy is a series of actions aimed at achieving goals and with an innovative and creative mindset to respond to developments that occur within the company and outside the company. A marketing strategy that can support product marketing to build customer loyalty is to use a marketing strategy that includes products, prices, promotions, people, processes and locations